Evaluation of 4H-4-chromenone derivatives as inhibitors of protein kinase CK2 - Prykhodko, A.O.; Yakovenko, O.Ya.; Golub, A.G.; Bdzhola, V.G.; Yarmoluk, S.M. (Біополімери і клітина, 2005)
Protein kinase CK2 (Casein Kinase 2) is a ubiquitous serine/threonine protein kinase involved in various cell signal transduction pathways. Thus, CK2 is a new perspective target for anticancer drugs. The receptor-based virtual screening of 2000 compounds from combinatorial library of 4H-4-chromenones has been carried out in search for CK2-inhibitors. 90 compounds have been chosen for biological testing based on the score values calculated by DOCK 4.0 software. It has been revealed, that 3-(4-chloro-3,5-dimethylphenoxy)-7-(4-methoxyphenylcarbonyloxy)-4-oxo-4H-chromene (12) and 7-(4-fluorophenylcarbonyloxy)-4-oxo-3-(4-phenylphenoxy)-4H-chromene (14) inhibit CK2 activity with IC50= 18.8 mM and IC50=22.4 mM, respectively.